How and why studies disagree about the effects of education on health: A systematic review and meta-analysis of studies of compulsory schooling laws. (September 2018) - Hamad, Rita; Elser, Holly; Tran, Duy C.; Rehkopf, David H.; Goodman, Steven N.
Abstract: Rich literatures across multiple disciplines document the association between increased educational attainment and improved health. While quasi-experimental studies have exploited variation in educational policies to more rigorously estimate the health effects of education, there remains disagreement about whether education and health are causally linked. The aim of this study was to conduct a systematic review and meta-analysis to characterize this literature, with a focus on quasi-experimental studies of compulsory schooling laws (CSLs). Articles from 1990 to 2015 were obtained through electronic searches and manual searches of reference lists. We searched for English-language studies and included manuscripts if: (1) they involved original data analysis; (2) outcomes were health-related; and (3) the primary predictor utilized variation in CSLs. We identified 89 articles in 25 countries examining over 25 health outcomes, with over 600 individual point estimates. We systematically characterized heterogeneity on key study design features and conducted a meta-analysis of studies with comparable health outcome and exposure variables. Within countries, studies differed in terms of birth cohorts included, the measurement of health outcomes within a given category, and the type of CSL variation examined. Over 90% of manuscripts included multiple analytic techniques, such as econometric and standard regression methods, with as many as 31 "primary" models in a single study. A qualitative synthesis of study findings indicated that educational attainment has an effect on the majority of health outcomes—most beneficial, some negative—while the meta-analysis demonstrated small beneficial effects for mortality, smoking, and obesity. Future work could focus on inconsistent findings identified by this study, or review the health effects of other types of educational policies. Highlights: Studies disagree on whether educational attainment causally affects health. We systematically review and meta-analyze quasi-experimental studies of compulsory schooling. There is substantial heterogeneity across outcomes, settings, and analytic methods. Education has mixed—but largely beneficial—effects on a range of health outcomes.